Factors associated with diet quality during COVID-19 pandemic among undergraduate students in Universiti Putra Malaysia - Omar, Noraida; Aripin, Dalina Puteri (Universiti Putra Malaysia Press, 2023)
Introduction: The COVID-19 preventive and restriction measures may disrupt an individual’s daily diet quality, potentially leading to obesity and other non-communicable diseases. This study aims to assess and determine factors associated with diet quality during the COVID-19 pandemic among undergraduate students at Universiti Putra Malaysia. Methods: 130 eligible undergraduate students, who participated in this cross-sectional study were assessed using Global Physical Activity Questionnaire (GPAQ), Depression, Anxiety, Stress Scale (DASS-21), and Rapid Eating Assessment for Participants short version (REAP-S). Self-reported sociodemographic characteristics, body weight status, and nutrition knowledge were evaluated. Statistical analysis was conducted using IBM SPSS 26.0 and p<0.05 was denoted as statistically significant. Results: Most of the respondents were female (76.2%), aged between 20-22 years old (64.6%), Bumiputera (80.0%), funded by loan or scholarship (73.1%), low socioeconomic status (60.0%), residing in the family household (57.7%), consumed home-cooked meals (58.5%), and used the e-hailing food services for 0-3 days/week (63.1%). There was an equal distribution in the year and program of study in every selected faculty. Most were having normal BMI status (54.6%), good nutrition knowledge (66.9%), sedentary (48.5%), less severe mental health status (85.4%), and good diet quality (62.3%). Nonetheless, throughout the study, only the anxiety subscale was associated with diet quality (r= -0.20, p<0.05). Conclusion: Perceived anxiety may lead to poor diet quality. Future studies could determine the food environment and food security faced by the students as these factors vary among individuals. It is also recommended to measure diet quality differences before, during, or after the pandemic.